COMPOSITION OF INDUSTRIAL DUSTS AND THEIR ECOTOXICOLOGICAL PROPERTIES - Samadova, Nilufar (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article gives an idea of dust as one of the natural phenomena, its structural structure, analyzes the degree of impact of dust on the environment and a living organism associated with production, describes the dangerous and harmful factors that dust can cause. In addition, dust protection measures and methods for quantifying dust are listed.